Elementary School Teachers' Strategies to Overcome Student Learning Burnout after the Pandemic - Rina Kurnia (Indonesian Journal of Innovative Teaching and Learning, 2024)
The problem of student learning burnout after the Covid-19 pandemic has become the teacher's duty and obligation to solve it, the teacher must be able to overcome student learning problems. The research aims to find out the strategies of primary school teachers to overcome post-pandemic student learning burnout. The research method uses field research. This research was conducted at SDN Selakopi Kabupaten Bandung Barat in 2021. Data collection used interviews, observation, and documentation. Data analysis using the comparative technique. The results showed that the problem of student learning burnout was caused by two factors, namely internal and external factors. The conclusion showed that an effort to overcome the problem of student learning burnout, requires teacher readiness, an appropriate curriculum, the availability of learning resources, as well as stable device and network support so that communication between students and teachers can be effective. The contribution of the results can be used as a source of information both theoretically and practically as well as material for consideration, support, and knowledge thinking for teachers in primary schools to overcome the problem of student learning difficulties.